High-frequency hearing loss, occupational noise exposure and hypertension: a cross-sectional study in male workers - Lai Jim-Shoung; Chen Ren-Yin; Huang Kuei-Hung; Liu Chiu-Shong; Chang Ta-Yuan; Bao Bo-Ying (BMC, 2011)
Abstract Background The association between occupational noise exposure and hypertension is inconsistent because of an exposure bias caused by outer-ear measurements of noise levels among workers. This study used hearing loss values (HLVs) measured at 4 kHz and 6 kHz in both ears as a biomarker to investigate the chronic effects of noise exposure on hypertension in 790 aircraft-manufacturing workers. Methods Participants were divided into a high hearing loss (HL) group (n = 214; average HLVs ≥ 30 decibel [dB] at 4 kHz or 6 kHz bilaterally; 83.1 ± 4.9 A-weighted decibel [dBA]), a median HL group (n = 302; 15 ≤ average HLVs < 30 dB at 4 kHz or 6 kHz bilaterally; 83.1 ± 4.4 dBA) and a low HL group (n = 274; average HLVs < 15 dB at 4 kHz or 6 kHz bilaterally; 82.2 ± 5.1 dBA) based on the results of pure tone audiometry. Multivariate logistic regressions were used to estimate the risk of hypertension between groups. Results The prevalence rates of hypertension were significantly higher in the high HL (43.5%; p = 0.021) and median HL (42.1%; p = 0.029) groups than in the low HL group (33.2%). The high HL and median HL workers had 1.48-fold (95% confidence interval [95%CI] = 1.02-2.15; p = 0.040) and 1.46-fold (95%CI = 1.03-2.05; p = 0.031) higher risks of hypertension relative to the low HL workers. Employment duration was significantly and positively correlated with the risk of hypertension among workers with average HLVs ≥ 15 dB at 4 kHz (p < 0.001) and 6 kHz (p < 0.001) bilaterally. Conclusions Our findings suggest that high-frequency hearing loss is a good biomarker of occupational noise exposure and that noise-induced hearing loss may be associated with the risk of hypertension.